Análise da utilização de uma super-heroina como recurso didático para o ensino de substâncias químicas: uma abordagem contextualizada do ensino de Química - SOUZA, Geane da Silva de (2022)
Among the countless possibilities of teaching chemistry in a playful way, the use of contextualized characters is a teaching strategy to arouse students' interest. In this direction, the present work presents a didactic resource of authorial production, produced based on the characteristic of the superheroine, Honey Lemon, disseminated in the daily life of the students' generation through the movie Big Hero 6. In this fiction, such a character uses a chemical bag that creates balls containing substances derived from the combination of chemical elements present in the periodic table. That said, the didactic material associates the products generated by the exchange with the combination of such elements in the composition of chemical substances. n addition, and brings some curiosities, in an interdisciplinary way, on the subject, highlighting applications in everyday life, it also contains a conceptual synthesis, a conceptual synthesis and activities to fix the information present in it. Thus, this research aims to analyze the use of the character as a didactic resource for the scope of the curricular component discipline Qchemistry developed in High School, in addition to evaluating its viability for helping in the teaching of Chemical Substances, based on the initial perception of a group of students about the material produced. Therefore, this work was developed with a group of 2nd year of high school, from a state public school in the municipality of Ananindeua/PA. The action was carried out during the period of mandatory Supervised Internship, which took place in the second semester of 2022. Through the results achieved, such as a better understanding of the content by the students, it is believed that the pedagogical material presents itself as an educational tool that supports the teaching of Chemical Substances, whose use can bring several benefits, as well as make the classes more of Chemistry more attractive, fun and comprehensive, favoring its understanding and learning.